1992
DOI: 10.1080/15298669291359717
|View full text |Cite
|
Sign up to set email alerts
|

POLYCYCLIC AROMATIC HYDROCARBONS (PAHs): A POSSIBLE CAUSE OF LUNG CANCER MORTALITY AMONG NICKEL/COPPER SMELTER AND REFINERY WORKERS

Abstract: A retrospective industrial hygiene investigation was undertaken to explain the cause of a statistically significant excess lung cancer mortality observed in a subset of a large cohort of nickel workers involved in mining, smelting, and refining of nickel and copper in Ontario. The focus of this paper is to demonstrate how an industrial hygiene follow-up assessment of an epidemiologic finding can help to identify a likely cause. Polycyclic aromatic hydrocarbons (PAHs) alone or in association with particulate an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

1997
1997
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 12 publications
0
13
0
Order By: Relevance
“…Within a copper-refinery subgroup with ≥25 years of work experience, lung cancer mortality was twice that expected (table 3) (13,29). Most of the excess, which was assumed to be work-related, was identified among workers from the tank-house, notably among lead welders and crane men, the latter handling electrodes from travelling cranes above the electrolytic tanks (29,34). a Four workers had furnace experience only, and 3 workers had furnace experience combined with ≤6 months in "non-dust" departments.…”
Section: Copper Cliff Copper Refinery Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Within a copper-refinery subgroup with ≥25 years of work experience, lung cancer mortality was twice that expected (table 3) (13,29). Most of the excess, which was assumed to be work-related, was identified among workers from the tank-house, notably among lead welders and crane men, the latter handling electrodes from travelling cranes above the electrolytic tanks (29,34). a Four workers had furnace experience only, and 3 workers had furnace experience combined with ≤6 months in "non-dust" departments.…”
Section: Copper Cliff Copper Refinery Studiesmentioning
confidence: 99%
“…The presence or concentration of soluble nickel in the electrolyte (20 g/L) was not communicated, and its possible contribution to the cancer excess was not discussed, neither in the epidemiological articles (13,29,43) nor in the industrial hygiene report (34). The latter focused on PAH exposure.…”
Section: Lack Of Focus On Soluble Nickelmentioning
confidence: 99%
See 1 more Smart Citation
“…On the basis of the detailed assessment, 20 papers were excluded according to the following systematic exclusion criteria: (i) if later updates were available (7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20), (ii) if it was a mortality statistic (21) and a cancer morbidity study was available (22), (iii) the papers republished data (23,24) that were already available elsewhere (25,26), (iv) the metal welded was atypical (lead) or the welders were resistence welders (27,28), and (v) the description of the welder population was insufficient (29).…”
Section: Ambroise Et Almentioning
confidence: 99%
“…We have shown that boilermakers are exposed to PAH and metals during the workweek, as indicated by repeated urinary sampling and measurement of 1-OHP and individual metal biomarkers of exposure. This is important because workers exposed to high levels of PAH, such as coke oven and aluminum industry workers, demonstrate an increased risk of cancer [IARC, 1983[IARC, , 1984[IARC, , 1985Bertrand et al, 1987;Verma et al, 1992]. Similarly, the carcinogenic potential of nickel and chromium has been well established for humans and experimental animals [IARC, 1990;Man, 1990;Hayes, 1997;Merzenich et al, 2001].…”
Section: Discussion Boilermakers Are Exposed To Metals and Pahmentioning
confidence: 96%